DETERMINAN MANIPULASI LAPORAN KEUANGAN DENGAN PENDEKATAN TEORI FRAUD HEXAGON (Studi Empiris pada Perusahaan Sektor Pertambangan yang terdaftar di Bursa Efek Indonesia Periode 2021-2023) - Velika Calista; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2025)
This study aims to examine the potential occurence of financial statement manipulation by utilizing the Fraud Hexagon Theory, which are proxied by financial instability, effective monitoring, total accruals, change in director, director-shareholder kinship, and concurrent positions of director toward financial statement manipulation, which will be measured using the Beneish M-Score. The population of this study consists of mining sector companies listed on Indonesia Stock Exchange (IDX) during the period 2021-2023. A total of 141 samples were analyzed using logistic regression with the assistance of SPSS version 29 software. The result of this study indicate that total accruals have a significant positive effect on financial statement manipulation. In contrast, financial instability, effective monitoring, change in director, director-shareholder kinship, and concurrent positions of director have no significant effect on financial statement manipulation.